Theological reflections on Ubuntology and African township Pentecostal Charismatic pastors during the Covid-19 pandemic - Mzondi, Modisa (Stellenbosch theological journal, 2022)
Globally, the 2019 novel coronavirus (2019-CoV) also known as Covid-19 affected every facet of human life. Everyone had to find new ways of doing things, as many nations introduced lockdown regulations as a means of curbing the spread of the corona virus that causes Covid-19. Included in the regulations was the closure of places of worship, which challenged the clergy from different denominations in South Africa to imagine how to do ministry in this new context called the "new normal". Not only that, African township Pentecostal-Charismatic pastors, like other members of the clergy, were also expected to guide and encourage church members in these times of uncertainty. In addition, they were also expected to care for church members, the community and for themselves and their families. This article reflects on how African township Pentecostal-Charismatic pastors may minister in the Covid-19 context by applying the modified theologies of Mashau and Kgatle's Ubuntology.